2010
DOI: 10.1310/hpj4504-314
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pharmacy Interventions at a Psychiatric Hospital: Comparison of Staff Pharmacists, Pharmacy Faculty, and Student Pharmacists

Abstract: Purpose Previous evidence suggests psychiatric pharmacists have improved patient symptoms and provide valuable information. However, there are limited recent data regarding clinical pharmacists performing interventions in a psychiatric setting and its effects on costs. Additionally, there are no data that differentiate between psychiatric hospital staff pharmacists' (HSP), faculty clinical pharmacists' (FCP), and student pharmacists' (SP) interventions. Therefore, the objective of this study is to evaluate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…This savings benefit, while similar to values reported in other studies, is still comparatively low given the significance of most interventions. [23][24][25][26][27] This is due primarily to the extreme subjectivity in calculating cost avoidance values. Because no standardized guidelines for economic evaluation of clinical interventions exist, the ability to generalize results from one study to another is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This savings benefit, while similar to values reported in other studies, is still comparatively low given the significance of most interventions. [23][24][25][26][27] This is due primarily to the extreme subjectivity in calculating cost avoidance values. Because no standardized guidelines for economic evaluation of clinical interventions exist, the ability to generalize results from one study to another is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Given that other studies have reported physician acceptance rates of student interventions of 60% to 95%, the probability of a 97% acceptance rate may be an overestimate and the result of decreased reporting of rejected interventions. 23,26,27 There could be several reasons for the high acceptance rate. Students may have felt that documenting a rejected intervention in essence was documenting a failure on their part.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 However, pharmacy students are capable of providing meaningful clinical services for the practice sites and can generate financial savings, which have been well documented in the literature. [5][6][7][8][9][10][11][12][13][14][15][16] Mersfelder and Bouthillier published a review of these studies dating back to the early 1990s. 17 Most either enrolled few students or were conducted over a relatively short period of time, often just a few months.…”
Section: Introductionmentioning
confidence: 99%